An Insight of Basal Cell Carcinoma Risk Factors - Almutairi, Rawan; Albazzali, Abeer (International Journal of Innovative Research in Medical Science, 2024)
Basal cell carcinoma (BCC), a type of non-melanoma skin cancer, is the most common cancer worldwide that originates within the outermost layer of skin, the epidermis. Overexposure to ultraviolet (UV) radiation from the sun considered the main cause of this disease. Many risk factors increase the chance of developing BCC including environmental, lifestyle, and genetic risk factors. These factors range from exposure to UV radiation, occupational hazards, chemical exposures, family history of BCC, genetic mutations, inherited skin conditions, sun exposure and tanning habits, smoking and tobacco use, to weakened immune system. Once the risk factors are understood, preventive steps such as mitigating sun exposure and avoiding harmful chemicals can be taken to significantly reduce the likelihood of developing the cancer. By identifying the people who are most likely to get the cancer and providing the necessary preventive options, such as regular check-ups and lifestyle advice, the burden of BCC can potentially be decreased.